Analisis Kadar Air dan Kadar Protein pada Surimi Ikan Patin (Pangasius, sp) dengan Variasi Pencucian dan Penambahan Tepung Sagu - Rosa Devitria; Harni Sepriyani (Jurnal Sains dan Kesehatan, 2021)
Patin Fish (Pangasius, SP), is one type of freshwater fish found in rivers in Riau Province. Patin fish is a source of high quality food, but it is a highly perishable food. Therefore, to overcome this need a way of preservation and processing that can maintain durability and not reduce the nutritional value that is by making surimi. In this research, the basic ingredients of patin fish are made with sago flour. Sago flour has different physical properties from tapioka flour and wheat flour so that it will increase the ability to from in surimi. Surimi is made with washing variations and added sago four. The results of this research were obtained from testing the chemical characteristics of surimi which were made with washing variations and obtained sago flour. The lowest and highest water conten of surimi is 52.1832% and 75.7656%. The lowest and highest protein content of surimi is 8.6631 % and 17.5487%.